Transformation of the pedagogical process in higher education during the quarantine - Pakhomova, Tetiana O.; Komova, Olena S.; Belia, Volodymyr V.; Yivzhenko, Yurii V.; Demidko, Evgeny V. (Linguistics and Culture Review, 2021)
The introduction of quarantine restrictions in the world has led to restrictions on many industries of both economic and social spheres of life. Education has not become an exception. The need to level the large number of students necessitated the search for alternative ways of organising educational and pedagogical processes. This is especially an issue for higher education institutions. Higher education institutions train specialists for many sectors of the economy and a significant break in the educational process due to quarantine restrictions could lead to a real collapse of the higher education system. This necessitates the search for ways to transform the pedagogical process in higher education institutions and the introduction of alternative mechanisms and methods of organising the educational process. The purpose of the study was to investigate the ways of transformation of the pedagogical process in higher education during the quarantine. A systematic algorithm for studying the transformation of the pedagogical process in conditions of quarantine and quarantine restrictions in higher education has been developed. The advantages and disadvantages of distance learning technologies of higher education have been identified. The main features of such remote technologies as Moodle, Google Classroom, and Zoom are analysed.